Determinan Dana Pihak Ketiga di 34 Provinsi Indonesia (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to: (1) identify and analyze the development of Third Party Funds (DPK), inflation, savings interest rates, Gross Regional Domestic Product (GRDP) at constant prices, and regional expenditure across Indonesian provinces during 2019–2023; and (2) examine the influence of inflation, savings interest rates, GRDP at constant prices, and regional expenditure on Third Party Funds in the same period. The research employs panel data regression analysis using EViews 12 for data processin.The results show that (1) the highest average growth of Third Party Funds (DPK) was recorded in South Kalimantan (11.89%), while the lowest was in Banten (-10.87%). The highest average inflation occurred in East Java (3.7%) and the lowest in Papua (2.1%). The savings interest rate peaked in 2019 at 1.17% and declined to its lowest level in 2022 at 0.37%. The highest GRDP growth was found in North Maluku (16.41%) and the lowest in West Papua (1.16%). Similarly, North Maluku also recorded the highest regional expenditure growth (14.08%), while West Papua experienced the lowest (-17.24%), reflecting economic disparities across regions in Indonesia. (2) The regression analysis reveals that GRDP at constant prices and regional expenditure have a significant and positive effect on Third Party Funds, while the savings interest rate has a significant and negative effect. In contrast, inflation shows no significant effect on Third Party Funds.